Effectiveness of applying Pain Nursing Guidelines on cancer Patient Health Outcomes - محمود, يوشع (Latakia University Journal -Medical Sciences Series, 2022)
Cancer-related pain is the most feared consequences of cancer and remains an important problem for cancer patient. Also, cancer patient having recurrent interaction with a variety of health providers, their pain is commonly uncontrolled. Cancer-related pain recognized as critical symptom that impact the quality of life of cancer patient. This study was conducted to evaluate the impact of Implementing Pain Nursing Intervention on cancer Patient health Outcomes. The study included 94-cancer patient with a pain rating of 4 or more. Patient received four educational sessions on pain assessment and management. Pain intensity, brief pain inventory, Pain management barriers management barriers were measured at baseline, one month, and three months post accrual. Patient experienced significant improvements in pain measures immediately post-intervention, and these improvements were sustained over time. Our study showed that the nursing intervention guideline was effective in reducing patient severity of pain barriers to pain management.